Using Mobile Phones to Present Medical Information to Hospital Patients - Vardoulakis, Laura Pfeifer; Karlson, Amy; Morris, Dan; Smith, Greg; Gatewood, Justin; Tan, Desney (CHI '12 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2012)
The awareness that hospital patients have of the people and events surrounding their care has a dramatic impact on satisfaction and clinical outcomes. However, patients are often under-informed about even basic aspects of their care. In this work, we hypothesize that mobile devices – which are increasingly available to patients – can be used as real-time information conduits to improve patient awareness and consequently improve patient care. To better understand the unique affordances that mobile devices offer in the hospital setting, we provided twenty-five patients with mobile phones that presented a dynamic, interactive report on their progress, care plan, and care team throughout their emergency department stay. Through interviews with these patients, their visitors, and hospital staff, we explore the benefits and challenges of using the mobile phone as an information display, finding overall that this is a promising approach to improving patient awareness. Furthermore, we demonstrate that only a small number of technology challenges remain before such a system could be deployed without researcher intervention.